A novel motion-editing technique using a timeline-based interface - Pantuwong, Natapon (My University, 2017)
This paper presents a timeline-based motion-editing system that enables users to perform motion-editing tasks easily and quickly. A motion sequence is summarized and displayed in the 3D environment as a set of editable icons. Users can edit the motion data by performing a sequence of operations on a single key frame or over an interval. The recorded sequence is then propagated automatically to a set of target key frames or intervals, which can be either user defined or system defined. In addition, we provide a simple interaction method for manipulating the duration of specific intervals in the motion data. Methods for combining and synchronizing two different motions are also provided in this system. In contrast with the previous work that allows only temporal editing, the proposed system provides editing functions for both geometry and temporal editing. We describe a user study that demonstrated the efficiency of the proposed system.